THE KNOWLEDGE OF EARLY CHILDHOOD EDUCATION TEACHERS ABOUT NATURAL DISASTER MANAGEMENT - Yeni Solfiah; Devi Risma; Hukmi -; Rita Kurnia (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2019)
Disaster management